Early Strength Of Shotcrete - Saw, Hla Aye (Curtin University, 2015)
This research studied the shotcrete strength development with time for worst and best conditions. The study included the minimum strength required of the shotcrete to support itself and how much time is required for that strength to develop after application including minimum strength required of the shotcrete to support an excavation. A field instrument was invented to indicate when re-entry conditions of the shotcrete have been met in situ.